1915 N.J. Laws 662-63 - (:unkn) unknown (My University, 1915)
Ch. 355, 1: Prohibited noncitizens from owning or possessing a shotgun or rifle. Punishable by fine and confiscation and resale of firearm. Not applicable to noncitizens owning at least $2,000 worth of property in the state.
Keywords: POSSESSION - DANGEROUS PERSONS